Increased heat tolerance of geothermal plants at the cost of reduced performance under cooler conditions - Jan-Niklas Nuppenau; Johan Ehrlén; Aelys M. Humphreys (BMC Ecology and Evolution)
Abstract Background All plants are influenced by the temperatures they are exposed to and fascinating adaptations to extreme temperatures have been described for many of them. However, the extent to which adaptation to thermal extremes is associated with costs, in terms of reduced performance at less or other stressful temperatures, is poorly known, especially for plants. In Iceland, there are two lineages of Agrostis stolonifera, one that occurs exclusively on geothermally heated soils (> 50 °C) and one that is only found on non-thermal soils. Since Iceland is a subarctic island, non-thermal areas surrounding the geothermal areas can get bitterly cold. This stark contrast in temperatures over short geographic distances provides an excellent system for studying adaptations to thermal extremes and potentially associated trade-offs. To test whether the geothermal lineage is more heat tolerant and whether this heat tolerance is associated with reduced performance under cooler conditions, we compared the heat and cold stress responses of the two lineages experimentally. Results No plants survived the hottest treatment (56 °C), only geothermal plants survived the second hottest treatment (49 °C) and geothermal plants also outperformed the non-thermal plants following the 46 °C treatment. In contrast, there were no differences in survival between geothermal and non-thermal plants under intermediate and cold conditions (41 °C, 21 °C and − 4 °C), but non-thermal plants outperformed geothermal plants under these conditions. Conclusions These results suggest that there is a trade-off between tolerating extreme heat and performance under cooler conditions, possibly indicating that geothermal A. stolonifera represents a specialised thermophilic lineage in Iceland. Our findings provide new empirical data on whole-plant responses to different thermal conditions, further understanding of the consequences of adapting to high and low temperature extremes, and raise new questions about the mechanisms, benefits and costs of thermal specialisation under different climatic conditions.